PRDM1 rs2185379, unlike BRCA1, is not a prognostic marker in patients with advanced ovarian cancer - Horackova, Klara; Vocka, Michal; Lopatova, Sarka; Zemankova, Petra; Kleibl, Zdenek; Soukupova, Jana (Disease markers. Section A, Cancer Biomarkers, 2024)
BACKGROUND: Ovarian cancer (OC) is mostly diagnosed in advanced stages with high incidence-to-mortality rate. Nevertheless, some patients achieve long-term disease-free survival. However, the prognostic markers have not been well established. OBJECTIVE: The primary objective of this study was to analyse the association of the suggested prognostic marker rs2185379 in PRDM1 with long-term survival in a large independent cohort of advanced OC patients. METHODS: We genotyped 545 well-characterized advanced OC patients. All patients were tested for OC predisposition. The effect of PRDM1 rs2185379 and other monitored clinicopathological and genetic variables on survival were analysed. RESULTS: The univariate analysis revealed no significant effect of PRDM1 rs2185379 on survival whereas significantly worse prognosis was observed in postmenopausal patients (HR = 2.49; 95%CI 1.90-3.26; p= 4.14 × 10 - 11) with mortality linearly increasing with age (HR = 1.05 per year; 95%CI 1.04-1.07; p= 2 × 10 - 6), in patients diagnosed with non-high-grade serous OC (HR = 0.44; 95%CI 0.32-0.60; p= 1.95 × 10 - 7) and in patients carrying a gBRCA1 pathogenic variant (HR = 0.65; 95%CI 0.48-0.87; p= 4.53 × 10 - 3). The multivariate analysis interrogating the effect of PRDM1 rs2185379 with other significant prognostic factors revealed marginal association of PRDM1 rs2185379 with worse survival in postmenopausal women (HR = 1.54; 95%CI 1.01-2.38; p= 0.046). CONCLUSIONS: Unlike age at diagnosis, OC histology or gBRCA1 status, rs2185379 in PRDM1 is unlikely a marker of long-term survival in patients with advance OC.
Keywords: Polymorphism, Single Nucleotide; Humans; lidé středního věku; Biomarkers, Tumor; BRCA1 Protein; jednonukleotidový polymorfismus; Female; Aged; nádory vaječníků; dospělí; Ovarian Neoplasms; senioři; lidé; Genotype; Positive Regulatory Domain I-Binding Factor 1; nádorové biomarkery; Adult; staging nádorů; ženské pohlaví; Middle Aged; protein PRDI-BF1; protein BRCA1; prognóza; Aged, 80 and over; genotyp; senioři nad 80 let; Neoplasm Staging; Prognosis